ПЕРШІ ДАНІ ЩОДО БІОЛОГІЧНИХ ОСОБЛИВОСТЕЙ AGRILUS PLANIPENNIS FAIRMAIRE, 1888 (COLEOPTERA: BUPRESTIDAE) НА ТЕРИТОРІЇ УКРАЇНИ - Kucheryavenko, T. V.; Skrylnik, Yu. Ye.; Davydenko, K. V.; Zinchenko, O. V.; Meshkova, V. L. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2020)
In the summer of 2019, the penetration of emerald ash borer (Agrilus planipennis Fairmaire, 1888) (Coleoptera: Buprestidae) (further EAB) in the territory of Ukraine was confirmed, although the presence of exit holes indicates its penetration no later than in 2018. Biological features of EAB have been studied in detail in its homeland (Far East of Russia) and in the regions of its introduction – the United States and European Russia. The aim of the research was to summarize the first information on the distribution, biology, and seasonal development of EAB in Ukraine. Inspection of forest stands and shelter belts show that at the end of the growing season in 2020 EAB spread to Markivsky, Troitsky, Bilokurakynsky, and Svativsky districts of Luhansk Region. Fraxinus pennsylvanica Marsh. is preferred tree species of EAB, and its area is 2.3 % of the forest area in the Forest & Hunting enterprises of Luhansk Region (3,771.2 ha) and is also widely spread in roadside and field-protective forest shelterbelts. However, inspection revealed also colonized with EAB trees of Fraxinus excelsior L. with almost twice as large area (7,474.3 ha) in the forests of the region. The maximal length of EAB egg galleries is 35 cm, maximal width is 4.7 mm, the depth of larvae placement in the wood during the winter is 15 mm. The size of the pupal chamber is from 8×2.8 mm to 16×4 mm, and the maximal depth of its placement is 5.7 mm. The size of the exit hole is from 2.4×2 mm to 3.6×2.1 mm. Mortality of EAB larvae in the galleries from different locations is from 3.4 % to 45.2 % from all assessed galleries. Most larvae are killed by birds. The parasitoid was reared from EAB-colonized branches, according to preliminary data, it is Spathius sp. (Braconidae). EAB prepupae successfully complete the development in the branches with a relative humidity of wood over 30 %. The rate of decrease in the relative humidity of the phloem depends on its initial humidity and branch diameter, which is proved experimentally. In the inspected foci, stratification of EAB populations into cohorts by seasonal development was supported and coincided with the publications on some other species. In May-June, the proportion of larvae of older instars and prepupae, and in July–August the proportion of younger larvae increased. In October–March the cohorts were presented almost equally. Further researches involve measuring the morphological parameters of EAB larvae collected in different foci and clarifying the dynamics of their age composition depending on the features and health condition of the stands.